Pengaruh Gaya Kepemimpinan dan Teknologi terhadap Prestasi Kerja Pegawai Dinas PMD Kabupaten Batang Hari - Siti Marina AZ; Ratna Ratna (Universitas Batanghari Jambi, 2023)
The purpose of this study was to determine the effect of Leadership Style, Work Behavior and Technology on Employee Work Performance at the PMD Office of Batanghari Regency. Where the method use disquantitative with multiple linear regression analysis tools, t-test, F-test and the coefficient of determination.Based on the results of statistical tests, partially only Leadership Style Variables thatpartially affect work performance with a t-count value of 2.945 while the t-table is 1.69726.because T count > from T table, then Ho is rejected and Ha is accepted, meaning that theindependent variable Leadership Style (X1) has a partial influence on the dependent variable or Work Achievement (Y). Simultaneous testing of X1, X2, X3 against Y, from the Anova table obtained the calculated F-value > F-table. Because the calculated F value is greater than F-table, it can be concluded that the variables of Leadership Style, Work Behavior and Technology have asimultaneous effect on Work Performance at the PMD Office of Batanghari Regency. and the results of the calculation of the coefficient of determination show that the influence of Leadership Style, Work Behavior and Technology on Work Performance is 16.9% and there maining 83.1% is influenced by other variables, which are not discussed in this study.